AN ANALYSIS OF FACTORS INFLUENCING THE AUTONOMOUS LEARNERS IN LEARNING ENGLISH - Zia Kemala (STKIP Siliwangi, 2016)
This study investigated the factors influencing the autonomous learners in learning English. This study was conducted in second grade of one senior high school in Bandung. This study employed a qualitative case study. Case study was deemed to be relevant for this study since it deals with specific phenomenon of autonomous learner as a single case which was analyzed and described. The data were obtained from the students which were collected through observation, questionnaire, and interview. After collecting the data, it was analyzed inductively based on qualitative data analysis and interpreted to answer the research question. The study revealed a finding related to the research question. It was found that the autonomous learners were influenced by five factors which are (1) motivation, (2) social environment, (3) task, (4) teacher and (5) material. These finding suggest that the teacher must encourage and promote students to become autonomous learner because students will get more benefit from becoming autonomous learners. Key words: Autonomous learner, influencing factors.